The Role of Vitamin D in the Occurrence and Severity of Coronary Artery Disease: Experience from Western India Study - Mathew, Cinosh; Thomas, Sara Mary (Research Developments in Medicine and Medical Science Vol. 5, 2023)
Background: The aim of this study was to investigate the potential correlation between Vitamin D deficiency (VDD) and the severity of coronary artery disease (CAD) in patients who were undergoing coronary angiography, given that VDD is a prevalent issue in developing nations and has been linked to atherosclerosis and CAD in recent research. Materials and Methods: In this descriptive cross-sectional study, consecutive patients with acute coronary syndrome or effort angina who underwent coronary angiography were enrolled. Vitamin D levels were measured and CAD was defined as at least one vessel stenosis >50% on coronary angiography. The study aimed to correlate Vitamin D levels with the severity and number of vessels involved as well as traditional CAD risk factors. Results: In the study, it was observed that 70.72% of the population suffered from Vitamin D deficiency. Patients were categorized based on their blood levels as having normal Vitamin D levels (> 30ng/ml), Vitamin D insufficiency (20-30ng/ml), and Vitamin D deficiency (<20ng/ml). In the group of patients with normal coronaries, only 2 out of the total had Vitamin D Deficiency, which accounts for 12.5%. Among those with Single Vessel Disease (SVD), 57 out of the total had VDD, accounting for 70.37%. In the group of patients with Double Vessel Disease (DVD), 91 out of the total had VDD, which accounts for 73.98%. For patients with Triple Vessel Disease (TVD), 36 out of the total had VDD, which accounts for 83.72%. The results indicated that Vitamin D levels were inversely correlated with significant coronary artery disease, both in terms of the number of vessels involved and their severity (p<0.001), as well as dyslipidemia (p=0.009). However, there was no significant correlation found between Vitamin D deficiency (VDD) and other conventional risk factors, including age, diabetes mellitus, gender, hypertension and smoking. Conclusion: The study found a high prevalence of Vitamin D deficiency among patients who underwent coronary angiography, and a significant correlation between Vitamin D deficiency and the prevalence and severity of CAD. However, further studies involving larger populations are necessary to determine if Vitamin D supplementation can prevent the progression of atherosclerosis and the development of CAD.